PENETAPAN KADAR SAPONIN PADA EKSTRAK DAUN LIDAH MERTUA (Sansevieria trifasciata Prain varietas S. Laurentii) SECARA GRAVIMETRI - Dumanauw Jovie Mien; Wullur Adeanne Carolin; Poli Anindita Firhani (Poltekkes Kemenkes Jakarta III, 2015)
Plants of Lidah mertua ( sansevieria trifasciata prain) can be used to treat diseases such asinfluenza, cough, inflammation of the respiratory tract, sprain, hit wound, rattlesnake bite, ulcers,and abscess .The leaves of Lidah mertuacontain saponin, and other compounds such as abamagenin, kardenolin , and polifenol .The purpose of this research is to determine the level of saponinon the leaf extractof Lidah mertua, typesansevieria trifasciata prain var .Laurentiiusinggravimetricmethod. .This was a descriptive research conducted in the farmakognosi laboratory ofPharmaceutical Major ofPoltekkes Kemenkes Manado. The sample of Lidah mertua leaves(sansevieria trifasciata prain Laurentii variant) was obtained from Pineleng Minahasa village.The determination of saponin levelof Lidah mertua extract leaves was conducted by extractingtheLidah mertua leaves using reflux with methanol solvent. Then the extract wasfractionationedwith a solvent successively with petroleum ether, ethyl acetate, n-Butanol. The n-Butanol extractwas evaporated and dissolved with methanol and saponin, then precipitated with dietyl ether.The saponin precipitation was determined gravimetrivelly. Result of study showed that Lidahmertua leaves, typesansevieria trifasciata prain var .Laurentii contained saponin with concentrationof 3.1258%. It is suggested that there will be further research to define the type of saponincontained in Lidah mertua leaves(Sansevieria trifasciata Prain var. Laurentii).